Carbon coated porous tin peroxide/carbon composite electrode for lithium-ion batteries with excellent electrochemical properties. (January 2015) - Li, Xu-Hui; He, Yan-Bing; Miao, Cui; Qin, Xianying; Lv, Wei; Du, Hongda; Li, Baohua; Yang, Quan-Hong; Kang, Feiyu
Abstract: A porous tin peroxide/carbon (SnO2 /C) composite electrode coated with an amorphous carbon layer is prepared using a facile method. In this electrode, spherical graphite particles act as supporter of electrode framework, and the interspace among particles is filled with porous amorphous carbon derived from decomposition of polyvinylidene fluoride and polyacrylonitrile. SnO2 nanoparticles are uniformly embedded in the porous amorphous carbon matrix. The pores in amorphous carbon matrix are able to buffer the huge volume expansion of SnO2 during charge/discharge cycling, and the carbon framework can prevent the SnO2 particles from pulverization and re-aggregation. The carbon coating layer on the outermost surface of electrode can further prevent porous SnO2 /C electrode from contacting with electrolyte directly. As a result, the repeated formation of solid electrolyte interface is avoided and the cycling stability of electrode is improved. The obtained SnO2 /C electrode presents an initial coulombic efficiency of 77.3% and a reversible capacity of 742 mA h g −1 after 130 cycles at a current density of 100 mA g −1 . Furthermore, a reversible capacity of 679 mA h g −1 is obtained at 1 A g −1 .